2018
DOI: 10.1186/s13019-018-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and clinical profile of infective endocarditis patients: an observational study experience from tertiary care center Karachi Pakistan

Abstract: BackgroundThe study analyzed microbiological and antimicrobial susceptibility profile of organisms isolated from patients with infective endocarditis (2015–17) and compared disease outcomes in cohorts of endocarditis patient with history of prior invasive vascular intervention (high risk group) vs those without (native valve group). We hypothesized that high risk group would be more likely to have severe disease outcomes.MethodsThis was a prospective cohort study (2015–17). All blood and cardiac tissue samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…MRSA accounted for about half of the S. aureus cases in our cohort. Although S. aureus has a wellknown propensity to develop resistance to methicillin and MRSA strains have been a universally recognized problem [ The overall in-hospital mortality was 18.1% in our study, which is in line with the high in-hospital death rates observed in other recent cohorts and indicates that IE remains a life-threatening condition requiring immediate and special attention [ 4,39,45,[72][73][74][75] ]. A signi cant decrease in the in-hospital mortality from 22.1-14.6% was noted comparing 2010-2015 to 2016-2020, which can be explained at least partially by the higher representation of patients with IVDU in the late cohort, who typically are of younger age and have less comorbidities [ 71,76,77 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…MRSA accounted for about half of the S. aureus cases in our cohort. Although S. aureus has a wellknown propensity to develop resistance to methicillin and MRSA strains have been a universally recognized problem [ The overall in-hospital mortality was 18.1% in our study, which is in line with the high in-hospital death rates observed in other recent cohorts and indicates that IE remains a life-threatening condition requiring immediate and special attention [ 4,39,45,[72][73][74][75] ]. A signi cant decrease in the in-hospital mortality from 22.1-14.6% was noted comparing 2010-2015 to 2016-2020, which can be explained at least partially by the higher representation of patients with IVDU in the late cohort, who typically are of younger age and have less comorbidities [ 71,76,77 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, S. aureus was the most prevalent pathogen in recent cohorts of patients with IE in Australia (45-53%)[ 21,[42][43][44][45] ]. The existing literature has repeatedly demonstrated increasing prevalence of staphylococcal IE particularly in the western world [ 6, 11,34,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…For the last two decades, a significant rise in incidence of infective endocarditis were observed worldwide (Tripodi et al, 2005;Marmolin et al, 2016;Shahid et al, 2018;Arregle et al, 2019;Chamat-Hedemand et al, 2020). Among 100,000 population, 2.6-7 cases of endocarditis have been reported per year, a significant proportion of which was contributed by streptococcal infections: with incidence of 17% in North America, 31% in other European countries, 39% in the South America, and 32% in rest of the world (Holland et al, 2016).…”
Section: Introductionmentioning
confidence: 99%